Cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy in patients with peritoneal carcinomatosis from colorectal cancer: The prognostic impact of baseline neutrophil-lymphocyte, platelet-lymphocyte and lymphocyte-monocyte ratios. (December 2020) - Zager, Yaniv; Hoffman, Aviad; Dreznik, Yael; Jacoby, Harel; Cordoba, Mordehay; Horesh, Nir; Nevler, Avinoam; Gutman, Mordechai; Berger, Yaniv
Abstract: Purpose: In this retrospective analysis we sought to determine if the preoperative neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and lymphocyte-monocyte ratio (LMR) were predictive of both operability and survival in those patients presenting with peritoneal carcinomatosis (PC) from colorectal cancer (CRC) who underwent cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC). Methods: Analysis included all patients admitted between 2009 and 2017 with PC from CRC who were treated with curative intent by CRS-Mitomycin C-HIPEC. Patients were assessed pre- and intra-operatively by the PC index (PCI) and by a completeness of cytoreduction (CC) score with calculation of Kaplan-Meier survival curves and multivariate analysis of prognostic factors. Discrimination was made for NLR >3.5, PLR >168.8 and LMR >4.4. Results: We identified 98 CRC patients undergoing 105 CRS-HIPEC procedures. There were no associations detected between NLR/PLR/LMR and the rates of incomplete or abandoned CRS cases. Overall survival (OS) after CRS-HIPEC was worse with high versus low NLR (19.9 mths v s. 45.7 mths, respectively; P = 0.009) and also with low versus high LMR (27.1 mths vs. 53.2 mths, respectively; P = 0.01). On multivariate analysis, a low LMR (P = 0.008), the preoperative CT PCI value (P = 0.004), poor tumor differentiation (P = 0.023) and the preoperative CEA level (P < 0.001) were all independent variables associated with a worse OS after surgery. Conclusions: The baseline LMR value may have potential value as a selection tool for CRS-HIPEC in patients with CRC-related PC. Highlights: Preoperative NLR/PLR/LMR have potential prognostic value in a range of cancers. We investigated their prognostic value among 98 CRC patients undergoing CRS-HIPEC. No associations were detected between preoperative NLR/PLR/LMR and incomplete CRS. Overall survival after CRS-HIPEC was worse with high NLR or low LMR. Low LMR was independently associated with a worse overall survival after surgery.